2018
DOI: 10.1111/jcal.12304
|View full text |Cite
|
Sign up to set email alerts
|

Can educational robotics introduce young children to robotics and how can we measure it?

Abstract: Studies have shown that educational robotics (ER) may impact student learning, especially in relation to STEM (science, technology, engineering, and mathematics) areas.In the STEM framework, particularly for younger children, the "E" and the "T" are considered to be missing letters, because few studies have concentrated on teaching and evaluating technology and engineering through ER activities. This study aimed to develop and test the efficacy of an ER protocol to teach robotics in a sample of 389 students, h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 30 publications
1
24
0
Order By: Relevance
“…Students use various tool platforms to assemble physical robots or program and debug robot programs. Studies have shown that the substantiality of, interaction with, and interest in robots can transform obscure STEM concepts into practical problems that can be operated, which greatly improves students' attitudes towards STEM (Carstro et al, 2018). The classroom is guided by practical problems or tasks, allowing students to learn modeling and algorithms, and to study how algorithms are applied in these systems.…”
Section: Improve the Role Of Educational Robots In Promoting Students' Stem Attitudesmentioning
confidence: 99%
“…Students use various tool platforms to assemble physical robots or program and debug robot programs. Studies have shown that the substantiality of, interaction with, and interest in robots can transform obscure STEM concepts into practical problems that can be operated, which greatly improves students' attitudes towards STEM (Carstro et al, 2018). The classroom is guided by practical problems or tasks, allowing students to learn modeling and algorithms, and to study how algorithms are applied in these systems.…”
Section: Improve the Role Of Educational Robots In Promoting Students' Stem Attitudesmentioning
confidence: 99%
“…Sullivan and Bers found that longer, but less intensive, exposure over an eight-week period can greatly increase children's understanding of robotics and programming 7 . Many other workshops of this type have found similar results 2,9,10 .…”
Section: Introductionsupporting
confidence: 71%
“…For example, Benitti (2012) mentions that apart from helping learners understand robotics, it can also help improve skills, such as problem-solving, logical thinking and scientific inquiry. Castro et al (2018) highlight another interesting observation that in a sample of 389 students selected to learn educational robotics, the success level of both girls and boys appeared to be the same. But while a few (Whittier & Robinson, 2007;Schopler & Toplis, 2008) experiment with using robotics to integrate subjects that are not related to physics and mathematics, most of the learning with educational robotics revolves around robotic concepts, such as "robot programming, robot construction, artificial intelligence, algorithm development and mechatronics" (Mitnik et al, 2008, p. 1).…”
Section: Diversity In the Way Kids Learn Programming In Schoolsmentioning
confidence: 70%